Modelagem tridimensional de problemas inversos em condução de calor: aplicação em processos de usinagem - Lima, Frederico Romagnoli da Silveira (2001)
This work proposes a methodology to obtain the transient cutting tool temperature. The physical phenomenon is treated by a three-dimensional analysis. The inverse heat conduction technique is proposed to estimate the generated heat flux on the rake face of the tool. This technique is based on conjugate gradient method with adjoint equation. The machining process is instrumented with thermocouples at the bottom face of the tool, opposite to its main rake face. The signals are automatically received and processed using a data acquisition system and a PC-Pentium. The direct solution is numerically solved using finite volumes method with the heat flux estimated. The experimental data are processed using a computational algorithm developed specifically for inverse heat flux estimation in machining processes. Experimental temperaturas are obtained during several cutting tests using cemented Carbide and ceramic tools. The influence of the cutting parameters on the temperatura distribution is verified. An error analysis of the results is also presented.